The influence of the ultrasonic treatment of working fluids on electrospun amorphous solid dispersions - Wang, Haibin; Lu, Yingying; Yang, Haisong; Yu, Deng-Guang; Lu, Xuhua (Frontiers in Molecular Biosciences, 2023)
Based on a working fluid consisting of a poorly water-soluble drug and a pharmaceutical polymer in an organic solvent, electrospinning has been widely exploited to create a variety of amorphous solid dispersions (ASDs). However, there have been very few reports about how to prepare the working fluid in a reasonable manner. In this study, an investigation was conducted to determine the influences of ultrasonic fluid pretreatment on the quality of resultant ASDs fabricated from the working fluids. SEM results demonstrated that nanofiber-based amorphous solid dispersions from the treated fluids (TASDs) exhibited better quality than the traditional nanofibers from untreated fluids in the following aspects: (1) a straighter linear morphology; (2) a smooth surface; and (3) a more evener diameter distribution. The fabrication mechanism associated with the influences of ultrasonic treatments of working fluids on the resultant nanofibers’ quality is suggested. Although XRD and ATR–FTIR experiments clearly verified that the drug ketoprofen was homogeneously distributed all over the TASDs and the traditional nanofibers in an amorphous state regardless of the ultrasonic treatments, the in vitro dissolution tests clearly demonstrated that the TASDs had a better sustained drug release performance than the traditional nanofibers in terms of the initial release rate and the sustained release time periods.